Glycaemic control and associated factors in adult patients with diabetes mellitus, South Sudan, 2021 - Joseph Lou K. Mogga; Stephen Loro; Stephen Gai; Moses Anyit; Robert Awu; Shaza Hadija; Jorum Aliti; Lawrence Biriwo; David Ameh (South Sudan Medical Journal, 2023)
Introduction: Many patients with diabetes mellitus are not attaining optimal glycaemic control, although the rate is unknown in South Sudan. Maintaining adequate glycaemic control is the most effective means of preventing complications associated with diabetes. This record review assesses the proportion of patients with diabetes on follow-up not adequately controlled using glycated haemoglobin (HbA1c) and describes associated factors.